Kinking of GaP Nanowires Grown in an In Situ (S)TEM Gas Cell Holder - David Krug; Maximilian Widemann; Felix Gruber; Shamail Ahmed; Thomas Demuth; Andreas Beyer; Kerstin Volz (Advanced Materials Interfaces, 2023)
Abstract Nanowires are a promising structure to create new defect‐free heterostructures and optoelectronic devices. GaP nanowires grown via the VLS mechanism using tertiary‐butyl phosphine (TBP) and trimethylgallium (TMGa) as precursors in an in situ closed gas cell heating holder are shown. This holder is a model system to investigate the processes in metal‐organic vapour phase epitaxy (MOVPE). GaP nanowires change their growth direction after random distances by producing kinks. Statistics of these kink angles show dominant values of around 70.5°, 109.5°, and 123.7°. A custom holder tip capable of holding a single heating chip is used to perform scanning precession electron diffraction (SPED) measurements on the nanowire kinks. The results show that the predominant kink angles result from micro twins of first and second order. Understanding the defect formation and resulting geometry changes in GaP nanowires can lead to increased control over their shape during growth and mark a huge step toward applicable nanowire devices.